Transcriptome of Sphaerospora molnari (Cnidaria, Myxosporea) blood stages provides proteolytic arsenal as potential therapeutic targets against sphaerosporosis in common carp - Hartigan, Ashlie; Kosakyan, Anush; Pecková, Hana; Eszterbauer, Edit; Holzer, Astrid S (BMC genomics, 2020)
BACKGROUND: Parasites employ proteases to evade host immune systems, feed and replicate and are often the target of anti-parasite strategies to disrupt these interactions. Myxozoans are obligate cnidarian parasites, alternating between invertebrate and fish hosts. Their genes are highly divergent from other metazoans, and available genomic and transcriptomic datasets are limited. Some myxozoans are important aquaculture pathogens such as Sphaerospora molnari replicating in the blood of farmed carp before reaching the gills for sporogenesis and transmission. Proliferative stages cause a massive systemic lymphocyte response and the disruption of the gill epithelia by spore-forming stages leads to respiratory problems and mortalities. In the absence of a S. molnari genome, we utilized a de novo approach to assemble the first transcriptome of proliferative myxozoan stages to identify S. molnari proteases that are upregulated during the first stages of infection when the parasite multiplies massively, rather than in late spore-forming plasmodia. Furthermore, a subset of orthologs was used to characterize 3D structures and putative druggable targets. RESULTS: An assembled and host filtered transcriptome containing 9436 proteins, mapping to 29,560 contigs was mined for protease virulence factors and revealed that cysteine proteases were most common (38%), at a higher percentage than other myxozoans or cnidarians (25-30%). Two cathepsin Ls that were found upregulated in spore-forming stages with a presenilin like aspartic protease and a dipeptidyl peptidase. We also identified downregulated proteases in the spore-forming development when compared with proliferative stages including an astacin metallopeptidase and lipases (qPCR). In total, 235 transcripts were identified as putative proteases using a MEROPS database. In silico analysis of highly transcribed cathepsins revealed potential drug targets within this data set that should be prioritised for development. CONCLUSIONS: In silico surveys for proteins are essential in drug discovery and understanding host-parasite interactions in non-model systems. The present study of S. molnari's protease arsenal reveals previously unknown proteases potentially used for host exploitation and immune evasion. The pioneering dataset serves as a model for myxozoan virulence research, which is of particular importance as myxozoan diseases have recently been shown to emerge and expand geographically, due to climate change.
Keywords: transkriptom; Fish Diseases; antiparazitární látky; Parasite; Virulence Factors; fylogeneze; Peptide Hydrolases; Phylogeny; In silico screening; Transcriptome; kapři; Myxozoa; faktory virulence; Proteases; Animals; Drug targets; objevování léků; Antiparasitic Agents; parazitární nemoci u zvířat; zvířata; nemoci ryb; Aquaculture; Parasitic Diseases, Animal; Carps; Drug Discovery; proteasy